ANALISIS YURIDIS KEPEMILIKAN HAK TANAH SEMPADAN PANTAI DI DAERAH PANTAI CARITA PANDEGLANG BANTEN oleh PT. MUTIARA HITAM PERTIWI - M DODDY NURHADI (PREMISE LAW JURNAL, 2017)
ABSTRACT Coastal Resources Management is intersectoral because marine sector covers the authority of some state institutions which work fields are related to oceans; for example, transportation, tourism and culture, energy and mineral resources, as well as marine and fishery. PT. Mutiara Hitam Pertiwi in Pandeglang, Banten, has set up cottages after buying a piece of land from the society; its purchase was conducted before the Head of Subdistrict. In fact, problems due to the land owner are frequently found. There was abrasion on the land that has decreased the resale value of the land or the cottage. The position of the land with coastal borders which was purchased from the people in Pandeglang Regency, Carita Village, Banten Province, according to the land entitlement, is the letter of notification by the Village Head or what is also called a temporary deed of ownership; which was gained from the people, sold to PT. Mutiara Hitam Pertiwi, managed into cottages and granted HGB (Building Rights). The title registration of the land with coastal borders has been in accordance with the general procedures so that the facts are valid. Keywords: With Coastal Borders, Ownership, Land